(untitled) (Research, Society and Development, 2021)
Objectives: To describe the incidence behavior and define the clinical, epidemiological and laboratory profile of congenital syphilis in the state of Amapá, Brazilian Amazon, from 2014 to 2018.Methods: A descriptive and cross-sectional study was conducted based on data provided by the Health Surveillance Secretariat of the estate of Amapá. The annual incidence rate for 1000 live births was calculated and its spatial distribution in the state was described. In addition, descriptive statistics of sociodemographic, clinical and laboratory variables, and inferential association statistics were performed, using Fisher’s Exact Test, for the relevant categorical variables. Results: There were registered 308 cases of congenital syphilis, with increasing incidence of the disease, and with Macapá city, the capital, representing 71.1% of the cases. In the profile of new borns, there was a predominance of race / brown color (47.37%), recent congenital syphilis (99.68%), and jaundice as the main symptom (68.5%). Regarding the maternal profile, it was characterized by women under 20 years old (31.35%), brown (76.3%), with incomplete 5th to 8th-grade education (25.97%), and housewives (82.94%). It was observed that prenatal care was performed in 72.4% of cases, but with a diagnosis prior to delivery in only 36.04%, the partner was not treated in 72.4%, and maternal treatment was inadequate in 63.3%.Conclusions: It was demonstrated an increasing behavior of the disease incidence, with a characteristic profile of involvement. It is essential to carry out and register diagnostic tests, as well as the solidification of prenatal services and continued training of health professionals.